2015
DOI: 10.1039/c5cc02694f
|View full text |Cite
|
Sign up to set email alerts
|

Gathering nanorings via Fe2+–bipyridine coordination

Abstract: Spontaneously precise organization of small structures into complex superstructures is ubiquitous and important in nature. But using small building blocks to mimic this process remains a challenge to scientists. Herein, we report the rational design of a bipyridine-derivative and applied it for the self-assembly of nanorings. The addition of Fe(2+) to the nanorings resulted in the assembly of the nanorings into supernanostructures via Fe(2+)-bipyridine coordination. HPLC, HR-ESI/MS, UV-vis, DLS, and TEM analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…On the basis of the self‐assembly system based on the reduction‐controlled condensation, Liang et al. further designed and realized a superstructure constructed by the coordination between Fe 2+ and the nanorings that were self‐assembled by CBT‐Cys(SEt) as shown in Figure a . To achieve the coordination, CBT‐Cys(SEt) was modified by a bipyridine motif in the lysine side chain, which would be revealed on the surface after the nanorings were assembled through the intramolecular condensation reaction, and this coordination would lead to the assembly of nanorings to form higher order nanostructure.…”
Section: Transformation Of Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the self‐assembly system based on the reduction‐controlled condensation, Liang et al. further designed and realized a superstructure constructed by the coordination between Fe 2+ and the nanorings that were self‐assembled by CBT‐Cys(SEt) as shown in Figure a . To achieve the coordination, CBT‐Cys(SEt) was modified by a bipyridine motif in the lysine side chain, which would be revealed on the surface after the nanorings were assembled through the intramolecular condensation reaction, and this coordination would lead to the assembly of nanorings to form higher order nanostructure.…”
Section: Transformation Of Nanostructuresmentioning
confidence: 99%
“…Upon Fe 2+ addition, the nanorings were gathered to form supernanostructures via Fe 2+ –bipyridine coordination. Reproduced with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Transformation Of Nanostructuresmentioning
confidence: 99%
“…Recently,t hey have demonstrated that the reduction-mediated nanorings could be furtherr egulated by Fe 2 + to self-assemble into superstructures via Fe 2 + -bipyridine coordination. [98] In addition to nanorings, oligomeric hydrogelss elf-assembled from GSH-controlling condensation between CBT and Cys were also reported, which might find broad applicationsi nr edox environment detection and long-term drug delivery. [99] Very recently,L in et al have utilized the biocompatibleC BT-Cys reaction-based self-assembly strategy to develop as mart 18 F-fluorinated PET tracer 6 for tumor imaging (Figure 10 a).…”
Section: Imaging Of the Redox Environmentmentioning
confidence: 99%
“…This simple assay was feasible to qualitatively measure the GSH levels in cell lysates and living cells. Recently, they have demonstrated that the reduction‐mediated nanorings could be further regulated by Fe 2+ to self‐assemble into superstructures via Fe 2+ –bipyridine coordination . In addition to nanorings, oligomeric hydrogels self‐assembled from GSH‐controlling condensation between CBT and Cys were also reported, which might find broad applications in redox environment detection and long‐term drug delivery …”
Section: Controlling the Self‐assembly To Build Multimodality Moleculmentioning
confidence: 99%